PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM TRANSAKSI E-COMMERCE MELALUI FACEBOOK - Mawarni, Rika (Fakultas Hukum Universitas Bangka Belitung, 2016)
Information technology and communication has developed so vast and one of the results is the convenience of e-commerce, a form of electronic transaction. Electronic transaction brings good and bag impacts to the parties involved. Both consumers and business owners are entitled to legal protection for their losses. Based on the result, it is concluded that there are four processes in the transaction implementation which are proposal, order, payment, and delivery. One of the benefits of doing transactions electronically is that the cost of marketing good and services is reduced considerably. The problems that can disrupt the transaction are swindles by irresponsible business owners and torts incurred by consumers that have made a deal in electronic transactions. Legal protection for parties in online transactions covers legal protection for consumers in the form of compensation and legal protection for business owners in the form of compensation and legal protection for business owners in the form of advance payment by consumers that have entered the online transactions.